Analysis of the regional potential for electricity generation through the energy recovery method of municipal solid waste - Lima, Vinicius de Jesus Almeida; Martins, Luís Oscar Silva; Escobar, Camila Ferreira (Brazilian Journal of Production Engineering, 2025)
Global population growth has generated a significant increase in the demand for electricity and in the production of Municipal Solid Waste (MSW). A sustainable alternative adopted globally, but still little explored in Brazil, is energy recovery via Waste-to-Energy (WTE) technology. WTE converts MSW into thermal or electrical energy through thermal processes, such as incineration, reducing the volume of waste and mitigating environmental impacts. In view of this, this study aimed to evaluate the regional potential for energy generation from MSW incineration. The gravimetric composition and Lower Calorific Value (LCV) of the waste were analyzed to estimate the electricity generation capacity in the different Brazilian regions. The results reveal that the Southeast and Northeast regions stand out for their greatest potential, while the national use of MSW can meet up to 3.1% of Brazil’s current electricity demand, demonstrating the relevance of this solution to diversify the energy matrix and reduce the environmental impacts associated with waste.